Alice goes north - Wallace, Karen; Dewar, Bob (London : A & C Black Pub., 2007)
After reading a magazine about Christmas, Alice the anteater leaves her jungle home and travels to the North Pole to ask Santa Claus a very important question.
2.8
K-3
Keywords: Anteaters -- Fiction; Christmas -- Fiction; Jungles -- Fiction; Santa Claus -- Fiction; Anteaters -- Fiction; Christmas -- Fiction; Jungles -- Fiction; Santa Claus -- Fiction; North Pole -- Juvenile fiction; North Pole -- Fiction; North Pole -- Fiction